Shock wave attenuation in a high-entropy alloy with pre-existing dislocation network - Hongcai Xie; Guoxiang Shen; Zhichao Ma; Wei Zhang; Hongwei Zhao; Luquan Ren (Journal of Materials Research and Technology)
High entropy alloys (HEAs), with their outstanding mechanical properties, hold promise as potential candidates for next-generation structural applications. However, the in-depth understanding of dynamic deformation mechanisms remains limited due to technological constraints in real-time detection of microstructural evolution at the atomic level. In present work, non-equilibrium molecular dynamics (NEMD) simulations were performed to study the shock response of FeCoNiCrCu HEAs with pre-existing dislocation network. The presence of initial dislocations was demonstrated to favor shock wave attenuation and stress relaxation in HEAs, which was a consequence of facilitated dislocation nucleation, multiplication, reaction, and accumulation behaviors. Especially, considerable immobile dislocations, Stair-rod and Hirth dislocations, occurred through dislocation reactions, contributing to the strain hardening level. Subsequent dynamic compression experiments demonstrated the dislocation multiplication mechanism in HEA, i.e., a high value of initial dislocation density led to a more efficient dislocation multiplication behavior, which further increased the contribution of dislocation strengthening. These findings provide pivotal insights for designing and developing HEAs with optimized properties under extreme environment.